Evolutionary ecomorphology of the Falkland Islands wolf Dusicyon australis. (10th January 2017) - Meloro, Carlo; Hunter, Jonathan; Tomsett, Louise; Portela Miguez, Roberto; Prevosti, Francisco J.; Brown, Richard P.
Abstract: The Falkland Islands wolf Dusicyon australis is an extinct canid that was once the only endemic terrestrial mammal to inhabit the Falkland Islands. There is still a puzzling picture of the morphological adaptations of this wolf that quickly evolved from its mainland fossil ancestor: Dusicyon avus . We employ a geometric morphometric approach to identify patterns of skull shape variation in extant canids and Dusicyon spp. The Falkland Islands wolf and its fossil ancestor show a more carnivorous feeding morphology than other South American foxes, and they cluster morphologically with jackals. This supports convergence in skull shape between Dusicyon and Old World canids, although the convergence is not as strong as that exhibited by their sister hyper‐ and hypocarnivorous taxa.